2018
DOI: 10.1177/2150132718815382
|View full text |Cite
|
Sign up to set email alerts
|

Access to Care for Homeless Veterans During Disasters

Abstract: Introduction: Since 1970, natural disasters have led to both temporary and permanent closures of multiple medical centers and outpatient clinics at the US Department of Veterans Affairs (VA) nationwide. Access to care during such events is critical for vulnerable populations, especially homeless veterans. As such, facility closures may disproportionately affect homeless veteran patients who are both more likely to experience adverse effects from disasters and face multiple barriers to care. Methods: A cross-se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Gender was not a factor in the likelihood of using VA homeless services (66% versus 60%, p = 0.52) 41 being referred to medical or mental health services, 10,51 in the number of days spent in inpatient hospitalization (IRR = 1.3, 95% CI: 0.42-4.04), 41 or in the persistent super-utilization of VA services (statistics not reported). 47 Similarly, other studies, which examined healthcare access found that gender was not a factor in the access to and care coordination experiences between VA healthcare and community care (OR = 0.92, 95% CI: 0.72-1.18), 37 in the ability to access healthcare in the event of a natural disaster (OR = 0.67, 95% CI: 0.28-1.58), 26 or the receipt of naloxone (18.9% for females versus 22.8% for males, p = 1.0) or medication (43.0% for females versus 37.8% for males, p = 1.0) for opioid addiction treatment. 40 There was also not an overall difference between males and females experiencing homelessness in their reported use of any VA homeless or social services (22.5% for females versus 16.5% for males, χ 2 = 0.48, p = 0.49).…”
Section: Comparison Of Male and Female Veterans' Access Or Use Of Hea...mentioning
confidence: 82%
“…Gender was not a factor in the likelihood of using VA homeless services (66% versus 60%, p = 0.52) 41 being referred to medical or mental health services, 10,51 in the number of days spent in inpatient hospitalization (IRR = 1.3, 95% CI: 0.42-4.04), 41 or in the persistent super-utilization of VA services (statistics not reported). 47 Similarly, other studies, which examined healthcare access found that gender was not a factor in the access to and care coordination experiences between VA healthcare and community care (OR = 0.92, 95% CI: 0.72-1.18), 37 in the ability to access healthcare in the event of a natural disaster (OR = 0.67, 95% CI: 0.28-1.58), 26 or the receipt of naloxone (18.9% for females versus 22.8% for males, p = 1.0) or medication (43.0% for females versus 37.8% for males, p = 1.0) for opioid addiction treatment. 40 There was also not an overall difference between males and females experiencing homelessness in their reported use of any VA homeless or social services (22.5% for females versus 16.5% for males, χ 2 = 0.48, p = 0.49).…”
Section: Comparison Of Male and Female Veterans' Access Or Use Of Hea...mentioning
confidence: 82%